2006
DOI: 10.1111/j.1525-1497.2006.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative status and risk of complications in patients with hip fracture

Abstract: In this study of older adults undergoing urgent surgery, potentially reversible abnormalities in laboratory and physical examination occurred frequently and significantly increased the risk of postoperative complications. Major clinical abnormalities should be corrected prior to surgery, but patients with minor abnormalities may proceed to surgery with attention to these medical problems perioperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 39 publications
1
55
0
3
Order By: Relevance
“…Although the optimal time for surgery after PFF in the elderly is not clear, most authors report that early surgical intervention (< 24, < 48, or < 72 hours) is associated with better prognosis and improved health status 15,31,32 . Delay to surgery prolongs hospital stay and increases the risk of pulmonary embolism, deep venous thrombosis, heart failure, urinary infection, and pressure sores 33,34,35 , thus delaying rehabilitation and increasing the risk of death. Table 2 Age-adjusted hazard ratios (HR) for one-year mortality after proximal femur fracture.…”
Section: Discussionmentioning
confidence: 99%
“…Although the optimal time for surgery after PFF in the elderly is not clear, most authors report that early surgical intervention (< 24, < 48, or < 72 hours) is associated with better prognosis and improved health status 15,31,32 . Delay to surgery prolongs hospital stay and increases the risk of pulmonary embolism, deep venous thrombosis, heart failure, urinary infection, and pressure sores 33,34,35 , thus delaying rehabilitation and increasing the risk of death. Table 2 Age-adjusted hazard ratios (HR) for one-year mortality after proximal femur fracture.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we found that 13% of the patients experienced major hospital complications 18 and a third of the patients were readmitted to the hospital within 6 months. Many were readmitted more than once.…”
Section: Discussionmentioning
confidence: 88%
“…Our findings suggest that the benefits of better process are not sustained if complications and hospital readmission occur. However, the opportunity to fully realize the benefits in functional outcome may exist given that modifiable risk factors have been described for hip fracture complications 18 and interventions have been developed to reduce readmissions in elderly patients. 44 In addition, our findings have important implications for research on and applications of quality measures in healthcare.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations